Protective effects of lemon and orange peels and olive oil on doxorubicin-induced myocardial damage via inhibition of oxidative stress and inflammation pathways - El-Refaiy, Amal I.; Salem, Zainab A.; Badawy, Abdelnaser A.; Dahran, Naief; Desouky, Muhammad A.; El-Magd, Mohammed A. (Frontiers in Pharmacology, 2025)
Background/aimCompounds originating from plants, especially citrus fruits and olive oil, have anti-inflammatory, cardioprotective, and antioxidant characteristics. Doxorubicin (DOX), an anthracycline antineoplastic, induces cardiotoxicity by generating free radicals. This study aimed to evaluate the cardioprotective effects of orange (OP) and lemon (LP) peels and olive oil (OO) against DOX-induced myocardial damage in rats.MethodsThirty adult male albino rats were randomly assigned to five groups, with six rats in each group. The control group was labeled Group I (Cnt), while Group II (DOX) got DOX intraperitoneally. Groups III, IV, and V were given a combination of DOX with OP, LP, or OO, respectively. After 28 days, cardiac biomarkers (AST, LDH, CK, cTnT), oxidative stress markers (NO, MDA), antioxidant enzyme activities (SOD, CAT, GPx), apoptotic genes (Bax, caspase 3, Bcl2), NFκB and inflammatory cytokines (TNFα, IL1β) were assessed. Histopathological analysis of the heart was also conducted.ResultsDOX-treated rats showed significant functional and structural cardiac damage, characterized by elevated AST, LDH, CK, cTnT, NO, MDA, Bax, caspase 3, NFκB, TNFα, IL1β and reduced SOD, CAT, GPx, and Bcl2 levels. These rats exhibited myocardial necrosis, inflammatory infiltration, mitochondrial damage, and myofibril atrophy. Treatment with OP, LP, or OO mitigated these effects, with OO providing the most substantial protection.ConclusionThese findings suggest that OP, LP, or OO can reduce DOX-induced cardiac toxicity by decreasing oxidative stress, apoptosis, and inflammation.